1993
DOI: 10.1080/00420989320080081
|View full text |Cite
|
Sign up to set email alerts
|

'Can Pay? Won't Pay?' or Economic Principles of 'Affordability'

Abstract: The term 'afford ability' has been gaining currency in housing policy debates, but neither government nor academic researchers have given much consideration to defining it. This paper considers what meanings have been given to the term affordability in practice and suggests a range of analytically more useful definitions. It argues from economic first principles that it is more logical to use some form of residual income definition than one based on a prescribed ratio of housing costs to income. Most researche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
145
0
8

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(156 citation statements)
references
References 2 publications
0
145
0
8
Order By: Relevance
“…Adult children staying with their families are believed to help the family earn more income [22]. Hence [15] in his study has classified working children under a separate unit from parents in his analysis while dependent children were considered as one unit with the parents [15] reiterated that values for housing and non-housing vary depending on size and age of household group consumption. Larger households require bigger houses and the attendant higher income needed to achieve the same level of wellbeing enjoyed by smaller households [7] found that households headed by women, senior citizens and single mothers bear higher housing cost liabilities [7] also proved that race and ethnicity of households indicated differing housing cost liabilities whereby black and Hispanic households faced housing problems and problematic neighbours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult children staying with their families are believed to help the family earn more income [22]. Hence [15] in his study has classified working children under a separate unit from parents in his analysis while dependent children were considered as one unit with the parents [15] reiterated that values for housing and non-housing vary depending on size and age of household group consumption. Larger households require bigger houses and the attendant higher income needed to achieve the same level of wellbeing enjoyed by smaller households [7] found that households headed by women, senior citizens and single mothers bear higher housing cost liabilities [7] also proved that race and ethnicity of households indicated differing housing cost liabilities whereby black and Hispanic households faced housing problems and problematic neighbours.…”
Section: Introductionmentioning
confidence: 99%
“…Debates on affordability measurement usually centre on accurate measurement of resources obtained by households i.e. whether income should be calculated on gross or after tax deduction to yield net income; and methods of calculation of sources of income [15] theorized that income measurement should be based on household net expendable income after all taxes have been deducted and housing benefits have been factored in as income. Housing benefits are subsidies given to deserving low income households to aid in housing costs and not to be used for other needs.…”
Section: Introductionmentioning
confidence: 99%
“…The general methodology for applying the two approaches is well known, and several studies have examined many particular aspects of its application such as: the income gap between renting and owning [39]; the definition of the cost of housing consumption in the short run or the analysis of affordability in the long run [13,15,48]; the type of households that are vulnerable to housing stress per age, location, composition, etc. [41]; and the housing standard based upon gross household income or disposable income [12].…”
Section: Methodology For the Assessment Of Housing Affordability In Mmentioning
confidence: 99%
“…An explicit ratio is also specified, although this has gradually shifted up over the Twentieth Century; for example, in Canada, it was 20 percent until the 1950s, 25% until the 1980s, and has been 30% since then. The ratio approach has been criticised because the value of this ratio is not the result of statistical models; it is just a 'rule-of-thumb' and, in any case, tends to apply the same ratio for any household type and consumption standard, so it may be misleading [13,15,30]. Nevertheless, if used in conjunction with other affordability measures, it may provide a useful starting point for examining affordability problems [31].…”
Section: Housing Affordability: Concept and Measurementioning
confidence: 99%
See 1 more Smart Citation